Developmental responses and survival of Anopheles stephensi larval stages at different salinity levels. (25th March 2022) - Jude, Justin; Gunathilaka, Nayana; Udayanaga, Lahiru; Fernando, Deepika; Premarathne, Prasad; Wickremasinghe, Rajitha; Abeyewickreme, Wimaladharma
Abstract: Background: Anopheles stephensi is a newly invaded vector in Sri Lanka. It has been identified in coastal areas in the northern and eastern parts of the country and evidences the ability to breed in brackish water environments. Methods: Laboratory investigations were conducted with batches of 100 first and third instar larvae exposed to a salinity gradient (0–40 ppt). Survival rates at 1 h, 24 h and until pupation were recorded for first and third instar larvae at different salinity levels. The experiment was repeated four times for both instars. Data were analysed using the general linear model and probit analysis. Results: Significant variations in adult emergence were observed from both larval stages at different salinity levels (p<0.05). The highest pupation rates were observed at 2.5 ppt salinity. The survival rate of first instar larvae after 24 h of salinity exposure was >80% up to 12.5 ppt, while 100% mortality was observed for from the ≥25 ppt level of salinity. More than 90% of the third instar larvae pupated from salinity levels <15 ppt. The lowest survival rate was reported as 15.8±2.47% at 25 ppt. Conclusions: This indicates a high potential of increasing density of A. stephensi in coastal ecosystems in lagoons and other saline water bodies. Hence it is high time to redesign vector control interventions for vector breeding in coastal ecosystems.